Updates of incretin‐related drugs for the treatment of type 2 diabetes. Issue 2 (14th November 2022) - Araki, Hirotaka; Matsumura, Takeshi; Furukawa, Noboru; Araki, Eiichi
Abstract : Mechanisms of dipeptidyl peptidase‐4 inhibitors, glucagon‐like peptide‐1 receptor agonists and glucagon‐like peptide‐1 receptor/glucose‐dependent insulinotropic polypeptide receptor dual‐agonist in glycemic control and/or weight loss.